Airborne flight time: A comparative analysis between the U.S. and China. (March 2023) - Liu, Ke; Zheng, Zhe; Zou, Bo; Hansen, Mark
Abstract: Actual airborne time (AAT) is the time between actual wheels-off and actual wheels-on of a flight. Given the ever-growing demand for air travel and growing flight delays, understanding the behavior of AAT is increasingly important for on time performance and delay propagation. Of particular interest is the comparison on AAT in different countries with varying air route structures, air traffic management systems, weather, and geography. This paper performs the first comparative empirical analysis of AAT behavior, focusing on the U.S. and China. The focus is on how AAT is affected by origin-destination (OD) distance, the possible pressure to reduce AAT from other parts of flight operations, hub status of departure/arrival airports, enroute and terminal traffic conditions, and convective weather. Econometric models are developed to quantify the impacts of factors on AAT behavior in China and the U.S., separately. The estimation results show that in both countries AAT is highly correlated with OD distance. Flight time in China is longer than that in the U.S. given the same OD distance which indicates a low effective speed may be the result of a low aircraft speed, or due to the flight experiencing metering, rerouting, holding or vectoring in Chinese airspace. In addition, we find that a flight has limited capability to make up for pre-departure delay. Sensitivity analysis of AAT to flight length and aircraft utilization is further conducted. Given the more abundant civil airspace, flexible routing networks, and efficient air traffic flow management (ATFM) procedures, we performed a counterfactual analysis to investigate how Chinese AATs would change if they were governed by the U.S. model. We find that this would result in significant efficiency gains for the Chinese air traffic system. On average, 13 min of AAT per flight would be saved. Systemwide fuel saving would amount to 326 million gallons with CO2 emission reduction of 2.7 million tons and direct airline operating cost saving of over 1.3 billion in 2016. Highlights: Perform empirical analysis of flight Actual Airborne Time (AAT) in the US and China. AAT is found highly correlated with OD distance. Flight time in the US is shorter than in China given the same OD distance. Flight has limited capability to make up for pre-departure delay. Efficiency gains could be achieved if applying the US model to the Chinese system.